A scooter acquires a velocity of 36 km h to the power of minus 1 end exponent in 10 seconds just after the start. calculate the accelaration of the scooter. 

Asked by deeptisingh25 | 29th Jun, 2014, 03:28: PM

Expert Answer:

From the equation of motion, we get,

v = u + a t

Initial velocity, u=0                  [ Since, body starts from rest ]

Final velocity, v=36 km/h = 36 x Syntax error from line 1 column 49 to line 1 column 73. Unexpected '<mstyle '.                  [1 km/h=Syntax error from line 1 column 49 to line 1 column 73. Unexpected '<mstyle '.]

Therefore, v = 10 m/s

t = 10 sec

v = u + a t

v - u = a t

Syntax error from line 1 column 49 to line 1 column 73. Unexpected '<mstyle '.

Syntax error from line 1 column 49 to line 1 column 73. Unexpected '<mstyle '.=a

Therefore, a = 1 m/s2

Hence, the acceleration of the scooter is 1 m/s2.

Answered by Faiza Lambe | 30th Jun, 2014, 08:56: AM